Physical and Chemical Inactivators Evaluation for the Puumala Virus Vaccine Technology Development - S. S. Kurashova; M. S. Egorova; M. V. Balovneva; A. N. Vetrova; A. S. Balkina; R. D. Teodorovich; V. G. Petrov; T. K. Dzagurova; E. A. Tkachenko (Эпидемиология и вакцинопрофилактика)
Relevance. Hemorrhagic fever with renal syndrome (HFRS) is leading among natural focal human diseases in Russia, the causative agents of which - orthohantaviruses - belong to the order Bunyavirales, family Hantaviridae. More than 98% of HFRS cases in Russia are caused by the Puumala virus. It is a serious zoonosis for which there is still no specific treatment. The WHO has not approved a vaccine. The aim of this study was to investigate the effect of formaldehyde, β-propiolactone, hydrogen peroxide, ultraviolet rays, gamma irradiation and thermal inactivation on the immunogenic activity of inactivated vaccine preparations against HFRS Materials and methods. To achieve this aim, experimental vaccine preparations based on the PUU-TKD/VERO strain of Puumala virus were prepared and inactivated using the methods described above. The time intervals required for complete inactivation of the virus were determined, and the effects of the inactivators on viral RNA and immunogenic activity of the vaccine preparations were evaluated in BALB/c mouse and Syrian hamster models. Results. According to our results, vaccine preparations inactivated by different chemical and physical methods, which differ significantly in the mechanism of the mechanism of interaction with the virus, show no significant differences in immunogenic activity, except for thermal inactivation. Conclusion. A certain advantage of β-propiolactone is the short virus inactivation time, its complete degradation into non-toxic compounds within a few hours, and the reduction of total protein content after sterilization filtration, which is probably due to less aggregation of virus particles and cellular proteins